Selected letters of Vernon Lee 1856-1935. Volume II, 1885-1889 - Geoffroy, Sophie; Gagel, Amanda; Hall, Crystal (London : Routledge, 2021)
Vernon Lee was the pen name of Violet Paget (1856-1935) - a prolific author best known for her supernatural fiction and her radical polemics. She was also an active letter writer whose correspondents include many well-known figures in fin de sicle intellectual circles across Europe. However, until now no attempt has been made to make these letters widely available in their complete form. This multi-volume scholarly edition presents a comprehensive selection of her English, French, Italian, and German correspondence -- compiled from more than 30 archives worldwide -- that reflect her wide variety of interests and occupations as a Woman of Letters and contributor to scholarship and political activism. Letters written in a language other than English have been expertly translated by scholars Sophie Geoffroy (from the French), Crystal Hall (from the Italian), and Christa Zorn (from the German). The edition focuses on those letters concerning the writing, ideas and aesthetics that influenced Lee's articles, books and stories. Full transcriptions of some 500 letters, covering the years 1856-1935, are arranged in chronological order along with newly written introductions that explain their context and identifies the recipients, friends and colleagues mentioned. Since scholarship on Lee's critical and creative output is still in the beginning stages, these letters will serve a purpose to students and researchers in a number of academic fields. In this second volume, covering the years 1885-1889, the 421 assembled letters follow Violet Paget-Vernon Lee in her early thirties. Recovering from the stinging reception of her first novel and from Annie Meyer's death, she turns to essay writing on aesthetics and ethics and ghost stories. After Mary Robinson's engagement to marry French orientalist Prof. Darmesteter, she travels to Spain, Gibraltar and Tangiers and briefly falls under the spell of the Orient. She also takes a liking to Scotland, and many of her close friends are Scottish --Alice Callander, Lady "Archie" (Janey Sevilla Archibald Campbell)--and so is her future partner Clementina Anstruther-Thomson. The letters reflect the expansion of her subject matter from cultural studies, art history and aesthetic philosophy. Her charity work in hospitals in Florence and her readings in Political Economy lead her thinking towards social reform and political issues. Her brother's mental illness and her own breakdown bring about an awareness of body and mind balance and a taste for outdoor pursuits (mountaineering; bicycling; horse riding; swimming) and for experimental psychology (rotating mirrors; hypnosis) and therapies (hydrotherapy). The Pagets move away from the city center of Florence into the Villa Il Palmerino, then in the countryside, where both Eugene and Vernon recover. Correspondents include Lee's parents, Matilda and Henry Ferguson Paget; her step-brother poet Eugene Lee-Hamilton; English poetess Mary Robinson; English poet Robert Browning; British novelist and journalist Ellen Mary Abdy-Williams; British social reform activist and editor Percy William Bunting; Irish journalist and activist Frances Power Cobbe; Irish scholar and novelist Bella Duffy; British eugenicist Karl Pearson; British publisher William Blackwood; Scottish writer Robert Louis Stevenson; American novelist Henry James; American connoisseur and arts patron Isabella Stuart Gardner; French translator and critic Marie-Thrse Blanc ("Th. Bentzon"); Lady Louisa Wolseley; Irish historian and activist Alice Stopford-Green; Italian Countess Angelica (Pasolini) Rasponi; Italian poet, writer and critic Enrico Nencioni; Italian novelist, essayist and critic Mario Pratesi; Italian editor and man of letters Francesco Protonotari; Italian painter Telemaco Signorini.
OCLC-licensed vendor bibliographic record.
Keywords: Lee, Vernon, -- 1856-1935 -- Correspondence; Lee, Vernon, -- 1856-1935 -- Friends and associates; LITERARY CRITICISM / General; LITERARY CRITICISM / Women Authors